2022
DOI: 10.12659/msm.938112
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Roles of Apelin and ELABELA Peptide Ligands in Cardiovascular Disease, Including Heart Failure and Hypertension

Abstract: Apelin and ELABELA (ELA), which are peptides belonging to the adipokines group, are endogenous peptide ligands of their receptor, APJ, which together constitute the apelinergic system. The apelinergic system is expressed in numerous human tissues and organs, including the heart, blood vessels, adipose tissue, central nervous system, lungs, kidneys, and liver. Apelin, being the most widely studied member of the apelinergic system, plays a key role in the cardiovascular system and exerts a pleiotropic effect in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Apelin plays a crucial role in the cardiovascular system. Under normal conditions, it enhances cardiac contractility, increases stroke volume, causes vasodilation, promotes diuresis and lowers blood pressure [33]. This system is expressed in various human tissues and organs, including the heart [33].…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Apelin plays a crucial role in the cardiovascular system. Under normal conditions, it enhances cardiac contractility, increases stroke volume, causes vasodilation, promotes diuresis and lowers blood pressure [33]. This system is expressed in various human tissues and organs, including the heart [33].…”
Section: Search Strategymentioning
confidence: 99%
“…Under normal conditions, it enhances cardiac contractility, increases stroke volume, causes vasodilation, promotes diuresis and lowers blood pressure [33]. This system is expressed in various human tissues and organs, including the heart [33]. Apelin exists in various isoforms, with apelin-36 being a prominent one.…”
Section: Search Strategymentioning
confidence: 99%
“…Apelin: Apelin is a neuropeptide produced as a precursor of 77-amino acid named preproapelin, which, after clivation at the C-terminus, yields the following active peptides: apelin-13, -16, -17, -19 and -36 [78]. The isoform -13 is the most biologically potent form, while all peptides are widely expressed in various human tissue types, predominantly in adipose tissue [79]. The functions of apelin are mediated by binding to a G-protein-coupled receptor called APJ [80].…”
Section: General Characteristics and Functions Of Adipokines And Thei...mentioning
confidence: 99%
“…Studies have shown that the expression of serum apelin and type Ⅱ transmembrane glycoprotein (CD40L) is closely related to the development of cardiovascular dis-eases; these compounds have attracted wide research attention [12][13][14]. Apelin is an endogenous ligand of angiotensin domain type 1 receptor-related protein.…”
Section: Introductionmentioning
confidence: 99%